BIMBINGAN KONSELING SEBAGAI SARANA PENGUATAN KARAKTER SOSIAL SISWA PADA PEMBELAJARAN IPS - Ester Helmin Dachi; Gelopatra Selan; Reniziduhu Giawa; Yedirius Laia; Andreas Buulolo; Renalis Ndruru; Emilia Sastrawati Zebua; Gresella Frisna Halawa; Kaminudin Telaumbanua (Universitas Nias Raya, 2023)
This study aims to examine the role of Guidance and Counseling (G&C) as a means of strengthening students’ social character in Social Studies (IPS) learning at SMP Swasta Kristen BNKP Teluk Dalam. The research employs a qualitative descriptive approach, involving G&C teachers, IPS teachers, and students as key informants. Data were collected through interviews, observations, and documentation, then analyzed thematically to identify the contribution of G&C in developing students’ social character. The findings reveal that G&C services play a significant role in shaping students’ social values, including empathy, tolerance, cooperation, responsibility, and positive interpersonal skills. The integration of G&C services with IPS learning enhances the internalization of social character through real social experiences in classrooms and group activities. Factors supporting the effectiveness of G&C include the competence of G&C teachers, collaboration among teachers and school staff, varied counseling methods, and active student participation. However, challenges such as limited service time and varied student responses need to be addressed for optimal program development. This study confirms that G&C is not only a medium for addressing personal issues but also a strategic tool for developing students’ social character. The findings can serve as a reference for schools in designing integrated G&C programs within IPS learning to foster students who are academically competent and socially responsible.